Conservative versus Surgical Management of Post-injection Sciatic Nerve Injury in Children - Ebrahim Shamout (Egyptian Spine Association, 2017)
Background Data: Intramuscular injection in the gluteal region represents one of the most important causes of sciatic nerve palsy. The main manifestation of most patients is foot drop and/or sciatic pain. Purpose: to evaluate the role of surgical exploration of post-injection sciatic nerve injury in reference to conservative treatment. Study Design: A retrospective cohort study. Patients and Methods: Reviewing our hospital medical records revealed 16 children with post injection sciatic nerve injury. All were included in this study. The mean age was 4.35±1.98 with range 1.5-8 years. Five children (31.3%) were females and 11 (68.8%) were males. All diagnosed by history, clinical examination, electrophysiological, functional assessment. All failed conservative treatment for 3 month and then either allocated for surgical exploration (N=10) or further conservative management (N=6) based on patients’ choice. All were followed routinely clinically and electrophysiologically. Results: Group I underwent surgical exploration and group II treated conservatively. The 3 months post-injection data were homogenous in both groups. Vasomotor changes, sensory loss and foot drop were the commonest manifestations in the 2 groups; right foot drop was more common than the left one (13 versus 3 children). Antibiotics and analgesics were the commonest causative agents of nerve injury in the studied children. Initial EMG were done for all cases at initial presentation and revealed sciatic nerve injury with complete degeneration of common peroneal nerve. Surgical exploration revealed peri-neural adhesions in all children. Follow up EMG at 3, 6 and 12 months shown complete improvement in 8 cases, partial improvement in one case and no improvement in one case in group-I. In group-II there was no reported improvement in 4 and partial improvement in 2 children with significant difference between the two groups (P=0.011). Conclusion: Surgical exploration of post injection sciatic nerve injury in children is feasible and effective management in reference to conservative methods. (2017ESJ142)